ALGEBRAIC STRUCTURES AS SEEN ON THE WEYL ALGEBRA - VAN OYSTAEYEN, FREDDY
The book develops some algebraic structure theory based upon properties observed on the Weyl algebra. Filtered and graded rings, finiteness conditions, localizations and rings of fractions, finiteness conditions on rings and modules, homological dimension and the Gelfand-Kirillov dimensions, simple Noetherian algebras and semisimples rings and modules are considered.